Adapting Protocols or Models for Use in Insulin-Requiring Diabetes and Islet Transplant Recipients - Ward, Glenn M.; Walters, Jacqueline M.; Gooley, Judith L.; Boston, Raymond C. (Frontiers in Endocrinology, 2021)
The authors’ perspective is described regarding modifications made in their clinic to glucose challenge protocols and mathematical models in order to study insulin secretion, insulin sensitivity and glucose effectiveness in patients who received Pancreatic Islet Transplants to treat Type I diabetes (T1D) and Impaired Awareness of Hypoglycaemia. The previous adaptations are described of protocols and models for use in T1D, and Type 2 Diabetes (T2D) that were the basis for studies in the Islet Recipients. In each group, the need for modifications, and how the protocols and models were adapted is discussed. How the ongoing application of the adaptations is clarifying the Islet pathophysiology in the Islet Transplant Recipients is outlined.